Parameter Optimization Of A Tubular Linear Type Reluctance Motor For High Thrust Force - Md Ghazaly, Mariam; Yeo, Chin Kiat; Chong, Shin Horng; Yusri, I; Tee, Siau Ping (Penerbit Universiti, UTeM, 2017)
-